Development Strategy of Food Crop Agriculture Sub-sector In Improving Farmers' Welfare - Suprianto Suprianto; Binar Dwiyanto Pamungkas; Abdul Rahim (Jurnal Ekonomi dan Studi Pembangunan, 2024)
This study aims to describe the priority strategy of agricultural sub-sector development in improving farmers’ welfare. The data used in this study were primary and secondary data. Secondary data included: GRDP of Sumbawa District, GRDP of NTB Province, and other supporting data for this study.  Primary data were: Experts Opinion Questionnaire or experts related to research problems. Respondents of this study were: bureaucrat respondents, academic respondents, farmer group respondents, and businessmen respondents. The determination of respondents used was purposive sampling technique which consisted of 30 respondents. The data analysis used was Process Hierarchy Analysis (AHP). The results of the study showed that: (1) Central government policies were a priority for achieving goals, compared to regional government policies. (2) Related to central government policy factor, protecting farmers was a priority compared to empowering farmers. (3) Regarding to protecting farmers, optimizing the role of Indonesia Logistics Bureau (BULOG) and implementing Warehouse Receipts was a priority. (4) Regarding the empowerment of farmers, the development of systems and facilities for marketing agricultural products was a priority. (5) The results of AHP showed that central government policies need to be considered and prioritized in crop agricultural sub-sector development strategy to improve farmers' welfare. Then to achieve the welfare of sub-criteria farmers, the protection of farmers must be prioritized. Furthermore, the alternative main priority in determining the strategy was optimizing the role of Indonesia Logistics Bureau (Bulog) and implementing Warehouse receipts.  Keywords: Strategy, Kesejahteraan Petani, Analythical Hierarchy Process (AHP).